INSTILLING JSN 45 AS STRENGTHENING NATIONALISM THROUGH LOCAL HISTORY LEARNING IN HIGH SCHOOL: Penanaman JSN 45 Sebagai Penguatan Nasionalisme Melalui Pembelajaran Sejarah Lokal di SMA - miskawi; Sariyatun (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
History education plays an important role in shaping national identity, historical awareness, and national character of students. One approach that can strengthen history education is the instillation of the Spirit and Values ​​of 45 (JSN 45) in history learning in high school. This study aims to analyze the concept, urgency, and implementation strategy of JSN 45 in strengthening local history learning for students. The approach used in this study is a literature study, by reviewing various academic sources, such as journals, books, and educational policy documents that are relevant to the Instillation of JSN 45 in local history learning. The analysis was carried out using the content analysis method to explore various concepts and practices that have been applied in history education based on national values. The results of the study show that the integration of JSN 45 in local history learning strengthens national identity, prevents social conflict, and instills the values ​​of unity and patriotism. Effective strategies include the use of digital media, project-based learning, and inquiry methods. However, the challenges faced include the lack of integration of local history in the curriculum, limited learning resources, and teacher readiness. Therefore, collaboration between the government, educators, and the academic community is needed to develop an inclusive and multicultural history curriculum.